Models of attention and dual-task performance as explanatory constructs in aphasia. - Hula WD; McNeil MR (Seminars in Speech & Language, 2008)
Aphasia has traditionally been viewed as a loss or impairment of language. However, evidence is presented suggesting that language mechanisms are fundamentally preserved and that aphasic language behaviors are instead due to impairments of cognitive processes supporting their construction. These processes may be understood as a linguistically specialized attentional system that is vulnerable to competition from other processing domains. We present two models of attention that focus on competition for central processing and discuss findings from dual-task studies of normal and aphasic performance. First, competing language and nonlanguage tasks appear to share limited-capacity, parallel processing resources. Second, aphasic individuals demonstrate slowed central processing that could be due to a reduction in processing capacity or ability to allocate that capacity. Third, the attention models discussed bear a coherent relationship to current models of language processing. Clinical implications of a cognitive processing account of aphasia are also considered.